MANAGEMENT OF PATIENTS WITH PULMONARY ARTERIAL HYPERTENSION IN THE PANDEMIC OF A NEW CORONAVIRUS INFECTION - T. V. Martynyuk; A. M. Aleevskaya; O. V. Rodnenkov; A. V. Zorin; A. M. Kasparova; S. N. Nakonechnikov; I. E. Chazova (Евразийский Кардиологический Журнал, 2020)
The pandemic of a new coronavirus infection – COVID-19 («Coronavirus disease 2019») has changed the routine management of patients with pulmonary arterial hypertension (PAH). Like patients with other chronic cardiovascular diseases, PAH patients are not at higher risk of a new coronavirus infection. However, in the current epidemiological situation, the problems of managing high-risk groups are sharply indicated, in which the severe course of COVID-19 with a higher lethality is more often noted. Undoubtedly, рatients with different forms of pulmonary hypertension belong to the high-risk group, considering both the presence of severe lifethreatening cardiovascular pathology and background pathology in cases of the associated forms of the disease.At the same time, the first foreign experience indicates a rather low incidence and relatively favorable course of COVID-19 in PAH, which allows to formulate a number of hypotheses that will be confirmed or rejected in the near future. The unique problems of managing patients with PAH are those associated with changes in generally accepted standards of medical care and patient routing, which is especially important for patients receiving PAH-specific drugs. The problems of a complex assessment of the risk of possible infection in the event of hospitalization or an outpatient visit of patients on the one hand, and on the other, the risk of PAH progression with a delay in starting treatment, are a dilemma that requires an individual solution. Based on an analysis of current data, this review summarizes the main approaches to managing patients with PAH in the current epidemiological situation.